Availability of subfertility management services in Colombo District, Sri Lanka - Gayani Gunawardhana; Sanjeeva Godakandage; Manuj Weerasinghe (College of Community Physicians of Sri Lanka, 2023)
Introduction: Affordable and accessible quality services reduce treatment defaults and improve patient satisfaction in subfertility management. Assessment of the available services is a necessity to advocate for the relevant authorities to improve services. Objectives: To assess the availability of subfertility management services at healthcare institutions in Colombo District, Sri Lanka Methods: This survey was performed in 2019 in 18 medical officer of health (MOH) units that provide field level healthcare; seven secondary and tertiary level government hospitals; and 32 registered private clinics/hospitals in Colombo District. Two separate checklists were developed for field-level and clinic/hospital-based services assessment. The interviews were performed to administer the checklist for clinical and administrative staff at different units of service provision. The availability of the services was presented as numbers and percentages. Results: Field-level availability of facilities; only 44.5% of MOHs had conducted awareness programmes on subfertility for the public during the past year and only 27.7% of MOHs had referred sub-fertile couples to secondary or tertiary hospitals for further management during the preceding month. Seminal fluid analysis (SFA) was available in 71.5% of the government sector and 84.3% of the private sector hospitals; abdominal and transvaginal ultrasound scans (USS) in 100% of government sector hospitals; and 93.7% of abdominal and 84.3% of transvaginal USS available in the private sector. Intra-uterine insemination (IUI) was available in 71.5% of the government sector hospitals but in only 40.6% of the private sector hospitals. Assisted reproductive technologies (ART) such as in vitro fertilization (IVF) was available in 12.5% of the private sector hospitals while none of the government sector hospitals provided this facility. Conclusions & Recommendations: The provision of field level facilities for subfertility was not satisfactory and less integrated. Notably, the ART services were available in the private sector hospitals predominantly. Rational public health policies need to be developed regarding the provision of field level and advanced care.